Implementasi Model Pembelajaran Kooperatif Teknik TSTS dengan Pendekatan Saintifik untuk Meningkatkan Kreativitas Berpikir dan Prestasi Belajar Menganalisis Klasifikasi Bisnis Ritel Kelas XI PMS 2 SMK Negeri 1 Lumajang - Tamami Tamami (FKIP Universitas Islam Jember, 2018)
The purpose of this study is to improve thinking creativity and learning achievement of Marketing Productive in class XI PMS 2 of SMK Negeri 1 Lumajang in the 2017/2018 Academic Year through the application of a cooperative learning model of two stay two stray techniques using the scientific approach. The type of research is Classroom Action Research. The research subject was XI PMS 2 students from SMK Negeri 1 Lumajang for the 2017/2018 Academic Year. Data collection techniques used were (a) observation, (b) interviews, (c) tests, and (d) documentation. Research procedures include (1) action planning; (2) implementation of actions; (3) observation; and (4) reflection. Based on the results of the study, it can be concluded that the cooperative learning technique model of TSTS using the scientific approach can improve thinking creativity and learning achievement. Keywords: cooperative, TSTS, scientific approach, creativity thinking, learning achievement.